PENGARUH PENERAPAN E-SPT PPN DAN E-FAKTUR TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KEMAMPUAN INTERNET SEBAGAI VARIABEL MODERASI - Jahormin Simarmata; Isrofatul Laili (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
This research aims to determine partially the application of the e-SPT PPN and the e-tax invoice effects on taxpayers compliance with internet capabilities as a moderating variable. The populations on this research are taxable entrepreneurs on Prama Tax Office Gambir Tiga Jakarta, who are still active in 2021 that uses the e-SPT PPN and e-tax invoice application. Sampling technics using the simple random sampling with totally 86 respondents. Data analyzed with multiple linier regression using tools of SPSS, 26 version . The result of this research sow that partially the application of e-SPT PPN and e-tax invoice has significant effect on tax compliance, while the internet skilled does not moderating e-SPT PPN and e-tax invoice application on taxpayer compliance.